Estimating the Demand for Business Training : Evidence from Jamaica - Maffioli, Alessandro; McKenzie, David; Ubfal, Diego (World Bank, Washington, DC, 2020)
Business training programs are typically offered for free. Charging for training provides potential benefits including financial sustainability, but little is known about how price affects the demand for training. This study conducted two experiments in Jamaica using the Becker-DeGroot-Marschak mechanism and take-it-or-leave-it offers to estimate the demand for training. Most entrepreneurs have a positive willingness to pay for training, but demand falls sharply as price increases: in the Becker-DeGroot-Marschak experiment, 76 percent of the entrepreneurs attend training when it is free, but only 43 percent attend when they are charged one-quarter of the cost, and only 11 percent when charged the full cost. Providing a credit option did not increase willingness to pay. Higher prices screen out poorer, older, and more risk-averse business owners, and those who expect to benefit less from training and have a low value of sales. However, charging a higher price increases attendance among those who pay, suggesting a psychological effect where paying for training makes firms value it more.